Pharmacokinetic/Pharmacodynamic Relationships of Tulathromycin Against Actinobacillus pleuropneumoniae in a Porcine Tissue Cage Infection Model - Yao, Lihua; Yang, Lan; Ling, Yuzhou; Wei, Yanzhe; Shen, Xiangguang; Ding, Huanzhong (Frontiers in Veterinary Science, 2022)
Tulathromycin is a semi-synthetic macrolide antibiotic that is highly effective in treating respiratory tract bacterial infections. We evaluated the in vivo antibacterial activity of tulathromycin against Actinobacillus pleuropneumoniae in piglets and determined its pharmacokinetic/pharmacodynamic (PK/PD) relationships using a tissue cage infection model. A. pleuropneumoniae (108 CFU/mL) was exposed to tulathromycin via intramuscular injection followed by collection of cage tissue fluids at various intervals. The percentage of time the drug concentration remained above the MIC divided by the dosing interval (%T＞MIC) was the best PK/PD index to describe the antibacterial efficacy of tulathromycin (R2=0.9421). The %T＞MIC values required to achieve 1-log10CFU/mL reductions and bactericidal activity (3-log10CFU/mL reduction) were 50.8 and 96.38%, respectively. These results demonstrated that maintaining %T＞MIC above 96.38 % achieved bactericidal activity and thereby optimized the clinical dosage.